Strain Distribution Along the Qilian Fold-and-Thrust Belt Determined From GPS Velocity Decomposition and Cluster Analysis: Implications for Regional Tectonics and Deformation Kinematics - Zhao, Guoqiang; Pan, Zhengyang (Frontiers in Earth Science, 2022)
The Qilian fold-and-thrust belt (QFTB) offers an excellent example to demonstrate the strain transition from strike-slip shearing to oblique crustal shortening, which plays an important role in dissecting the stress propagation of Indian-Eurasian convergence from the plateau interior to the surrounding blocks. Various geological or numerical models have attempted to describe the regional tectonic characteristics of the QFTB. However, these models only interpret one or part of the deformation behaviors in the QFTB, and the strain distribution across and along the QFTB as well as its deformation kinematics remain to be determined. Therefore, in this work, we applied the method of velocity decomposition and cluster analysis using combined GPS data to determine the strain partition or accommodation in different parts of the QFTB, as well as tectonic relationships with surrounding blocks, which will contribute to distinguishing which model is more suitable for delineating the present-day deformation kinematics of the QFTB. Our analysis indicates that the western part of the QFTB is dominated by mainly crustal shortening perpendicular to the trend of the QFTB, coupled with lateral extension along the trend of the QFTB, while the eastern part of the QFTB is characterized mainly by lateral extrusion owing to the impact of two large eastward-striking left-slip faults (East Kunlun fault and Haiyuan fault), which are accommodated by an obvious velocity gradient boundary belt centered on two diamond basins (Qinghaihu and Gonghe basins) associated with their boundary faults. The active tectonics of the QFTB are obviously divided into two distinct groups: one group is a pure shear–strain pattern, accounting for strong crustal shortening in the western part of the QFTB; and the other group is a simple shear–strain pattern, accounting for the obvious lateral extrusion in the eastern part of the QFTB.